PENGENALAN KEGIATAN MENGGUNTING UNTUK MENINGKATKAN KEMAMPUAN MOTORIK HALUS PADA ANAK USIA 4 - 5 TAHUN DI RA HIDAYATUSSYARIF - Jaya, Ilham; Sipakyah, Sri (LPPM Universitas Bina Bangsa, 2024)
This research was motivated by the existence of fine motor skills in children at RA Hidayatussyarif, resulting in many students having difficulty using finger or hand muscles such as coloring, holding a pencil and cutting. This research aims to improve fine motor skills in children aged 4-5 years in RA HIDAYATUSSYARIF Selamat NTB. This research is classroom action research. The research subjects used three cycles, namely pre-cycle, Cycle 1 and Cycle 2 with a total of 16 children, consisting of 6 boys and 10 girls. Data collection uses observation and documentation techniques. From the research results, it was concluded that there was an increase from pre-cycle, cycle 1 to cycle 2